Finding new ways to practise critically: applying a critical reflection model with Australian health promotion practitioners. Issue 5 (3rd September 2017) - Tretheway, Rebecca; Taylor, Jane; O'Hara, Lily
Abstract: Greater support is required in health promotion for practitioners to adopt critical approaches to their practice. Despite recognition of the role that critical reflection can play in supporting critical practice, it is underdeveloped in health promotion. This pilot study aimed to explore the use of critical reflection with health promotion practitioners. Critical postmodernism provided the theoretical perspective and critical reflection methodology guided the study. The data collection method involved the application of a critical reflection model via in-depth semi-structured interviews with two health promotion practitioners who were recruited using purposive sampling. Critical postmodernism and critical health promotion values and principles were the thematic frameworks used to analyse the data. Four types of assumptions were identified across both participants' narratives: binary opposites and dichotomous thinking; identity and othering; professionalism; and power. Two key themes that evidenced these assumptions were conceptualising power as a commodity, and identity in the Aboriginal and Torres Strait Islander context. Both traditional and critical health promotion practice approaches were evident in participants' practice. The process of engaging in critical reflection resulted in positive outcomes for the practitioners, including the identification of new, more critical ways of practising. Critical reflection provides a process for developing critical health promotion practice. The designation of critical reflection as a core health promotion competency may enhance the development of critical health promotion. Further research is needed to develop and test a critical reflection model incorporating the values and principles of health promotion with a larger sample of practitioners.